Microscopic distinction of wood between two Pinus species; P. Halepensis and P. Brutia - Kakavas, Konstantinos; Birbilis, Dimitris; Chavenetidou, Marina (European Journal of Applied Sciences, 2022)
This research aims to develop a pine-wood identification methodology concerning Pinus halepensis (Aleppo pine) and Pinus brutia (Turkish pine), based on microscopic observations and anatomical features that could be used to identify and distinguish the above two species (in particular the dimensions of the rays). We concluded that the maximum ray height of the Pinus halepensis wood is lower than that of the Pinus brutia wood (18 vs. 26 cells respectively). The average ray height of Pinus halepensis wood is lower than that of the Pinus brutia wood. It’s the first attempt to identify these two different Pinus species.